SEMI‐ROLLED LEAF 10 stabilizes catalase isozyme B to regulate leaf morphology and thermotolerance in rice (Oryza sativa L.). Issue 4 (23rd January 2023) - Wang, Jiajia; Xu, Jing; Wang, Li; Zhou, Mengyu; Nian, Jinqiang; Chen, Minmin; Lu, Xueli; Liu, Xiong; Wang, Zian; Cen, Jiangsu; Liu, Yiting; Zhang, Zhihai; et al.
Summary: Plant architecture and stress tolerance play important roles in rice breeding. Specific leaf morphologies and ideal plant architecture can effectively improve both abiotic stress resistance and rice grain yield. However, the mechanism by which plants simultaneously regulate leaf morphogenesis and stress resistance remains elusive. Here, we report that SRL10, which encodes a double‐stranded RNA‐binding protein, regulates leaf morphology and thermotolerance in rice through alteration of microRNA biogenesis. The srl10 mutant had a semi‐rolled leaf phenotype and elevated sensitivity to high temperature. SRL10 directly interacted with catalase isozyme B (CATB), and the two proteins mutually increased one other's stability to enhance hydrogen peroxide (H2 O2 ) scavenging, thereby contributing to thermotolerance. The natural Hap3 (AGC) type of SRL10 allele was found to be present in the majority of aus rice accessions, and was identified as a thermotolerant allele under high temperature stress in both the field and the growth chamber. Moreover, the seed‐setting rate was 3.19 times higher and grain yield per plant was 1.68 times higher in near‐isogenic line (NIL) carrying Hap3 allele compared to plants carrying Hap1 allele under heat stress. Collectively, these results reveal a new locus of interest and define a novel SRL10–CATB based regulatory mechanism for developing cultivars with high temperature tolerance and stable yield. Furthermore, our findings provide a theoretical basis for simultaneous breeding for plant architecture and stress resistance.